Environmental enrichment intervention for Rett syndrome: An individually randomised stepped wedge trial - Downs, Jennepher; Rodger, J.; Li, C.; Tan, X.; Hu, N.; Wong, K.; De Klerk, N.; Leonard, H. (BioMed Central Ltd., 2018)
Background: Rett syndrome is caused by a pathogenic mutation in the MECP2 gene with major consequences for motor and cognitive development. One of the effects of impaired MECP2 function is reduced production of Brain Derived Neurotrophic Factor (BDNF), a protein required for normal neuronal development. When housed in an enriched environment, MECP2 null mice improved motor abilities and increased levels of BDNF in the brain. We investigated the effects of environmental enrichment on gross motor skills and blood BDNF levels in girls with Rett syndrome. Methods: A genetically variable group of 12 girls with a MECP2 mutation and younger than 6 years participated in a modified individually randomised stepped wedge design study. Assessments were conducted on five occasions, two during the baseline period and three during the intervention period. Gross motor function was assessed using the Rett Syndrome Gross Motor Scale (maximum score of 45) on five occasions, two during the baseline period and three during the intervention period. Blood levels of BDNF were measured at the two baseline assessments and at the end of the intervention period. The intervention comprised motor learning and exercise supplemented with social, cognitive and other sensory experiences over a six-month period. Results: At the first assessment, the mean (SD) age of the children was 3 years (1 year 1 month) years ranging from 1 year 6 months to 5 years 2 months. Also at baseline, mean (SD) gross motor scores and blood BDNF levels were 22.7/45 (9.6) and 165.0 (28.8) ng/ml respectively. Adjusting for covariates, the enriched environment was associated with improved gross motor skills (coefficient 8.2, 95%CI 5.1, 11.2) and a 321.4 ng/ml (95%CI 272.0, 370.8) increase in blood BDNF levels after 6 months of treatment. Growth, sleep quality and mood were unaffected. Conclusions: Behavioural interventions such as environmental enrichment can reduce the functional deficit in Rett syndrome, contributing to the evidence-base for management and further understanding of epigenetic mechanisms. Environmental enrichment will be an important adjunct in the evaluation of new drug therapies that use BDNF pathways because of implications for the strengthening of synapses and improved functioning. Trial registration: ACTRN12615001286538.